2012
DOI: 10.1002/pon.3145
|View full text |Cite
|
Sign up to set email alerts
|

Psycho‐oncological care in certified cancer centres—a nationwide analysis in Germany

Abstract: Compared with non-certified centres, the proportion of patients receiving psycho-oncological care in certified cancer centres has increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 14 publications
1
36
0
12
Order By: Relevance
“…Certified cancer centers documented an uptake rate of 37.3% [10], compared to 32.5% estimated by a survey of acute care hospitals, mostly certified cancer centers, in breast cancer [11] and 11% in a large non-certified cancer center [12]. A populationbased study with long-term survivors of breast cancer reported that 16% had received ambulatory psychotherapy or psychosocial counselling [13].…”
Section: Discussionmentioning
confidence: 98%
“…Certified cancer centers documented an uptake rate of 37.3% [10], compared to 32.5% estimated by a survey of acute care hospitals, mostly certified cancer centers, in breast cancer [11] and 11% in a large non-certified cancer center [12]. A populationbased study with long-term survivors of breast cancer reported that 16% had received ambulatory psychotherapy or psychosocial counselling [13].…”
Section: Discussionmentioning
confidence: 98%
“…However, the reality may be quite different as hospitals have often been reluctant to establish such services due to financial restrictions. Therefore, in a recently published study, the data from 456 certified cancer centers were analyzed addressing the quality of implementation of professional psychosocial care [20]. The data available show that psycho-oncological care has been improved in acute care, although there are still gaps in demand and delivery of services across urban and rural areas [21].…”
Section: Psychosocial Support For Cancer Patients In Healthcarementioning
confidence: 99%
“…Comparison with other center types that have the same criteria show that implementation is higher in breast and colorectal cancer centers [20,21], which may be due to gender-specific patient preferences.…”
Section: Discussionmentioning
confidence: 87%